Stratigraphy, palynology and organic geochemistry of the Devonian-Mississippian metasedimentary Albergaria-a-Velha Unit (Porto-Tomar shear zone, W Portugal) - Machado, Gil (2011)
The Albergaria-a-Velha Unit is one of several tectonostratigraphic out-of-sequence units of the metamorphic belt associated with the Porto-Tomar shear zone (Ossa-Morena Zone, W Portugal). It is composed of considerably deformed - very low grade - metasediments, namely shales, siltstones and rare fine sandstones. In this work we present new sedimentological and biostratigraphical data that suggest the Albergaria-a-Velha Unit was deposited from the (?)early Frasnian to the Serpukhovian in a distal marine environment, where turbiditic and basinal sedimentation prevailed. Palynofacies analysis and lithological data point to a gradual increase of terrestrial input, suggesting a prograding system. Detrital framework data is indicative of a stable cratonic sediment source area composed of low grade metamorphic rocks. The timing of the onset of the Porto Tomar shear zone activity and consequently its influence on the sedimentation of this unit is discussed. Organic petrology and geochemistry data indicate that the Albergaria-a-Velha Unit is within the dry gas window in terms of hydrocarbon generation ranges.